If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 9 = 1x + 6 Reorder the terms: 9 + 2x = 1x + 6 Reorder the terms: 9 + 2x = 6 + 1x Solving 9 + 2x = 6 + 1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 9 + 2x + -1x = 6 + 1x + -1x Combine like terms: 2x + -1x = 1x 9 + 1x = 6 + 1x + -1x Combine like terms: 1x + -1x = 0 9 + 1x = 6 + 0 9 + 1x = 6 Add '-9' to each side of the equation. 9 + -9 + 1x = 6 + -9 Combine like terms: 9 + -9 = 0 0 + 1x = 6 + -9 1x = 6 + -9 Combine like terms: 6 + -9 = -3 1x = -3 Divide each side by '1'. x = -3 Simplifying x = -3
| 3x-7-1x=15-2x-6 | | 3x--x+14=30 | | 2(5c+2)=2(2c+11) | | 20/40=r/5 | | 3m+5=3 | | 1.3c=4.5 | | x-15x+18=3-10x | | 87=1+4x | | 256-8t=-30 | | 6(2c+2)=5(2c+9) | | (4x+2)+(8+x)=180 | | 1/3c=4.5 | | 4y+4x=14 | | 2x+-2=-0.5x+2 | | 143=3+5x | | x+-2=-0.5+2 | | 2x+(21+x)=90 | | 2(x+3)+3(x+2)=4x+17 | | 3-27=4a | | -3x-14x-21=1 | | 2/3(x¥ | | 6.1x+48.8=97.6 | | 3y-4x=2y-2x+10 | | p^(3/8)=5 | | (23+10x)onehalf= | | 3n+7-2n-14=4n+8 | | 7.27x+21.81=43.62 | | -3+5x+7=2x+4+3x | | 3.2x=-6.4 | | x-4x-1=12 | | -1/24 | | 2+4y=6y |